EMCCD photometry reveals two new variable stars in the crowded central region of the globular cluster NGC 6981 - Skottfelt, J.; Bramich, D.; Figuera Jaimes, R.; Jorgensen, U.; Kains, N.; Harpsoe, K.; Liebig, C.; Penny, M.; Alsubai, K.; Andersen, J.; Bozza, V.; Browne, P.; et al. (EDP Sciences, 2013)
Two previously unknown variable stars in the crowded central region of the globular cluster NGC 6981 are presented. The observations were made using the electron multiplying CCD (EMCCD) camera at the Danish 1.54 m Telescope at La Silla, Chile. The two variables were not previously detected by conventional CCD imaging because of their proximity to a bright star. This discovery demonstrates that EMCCDs are a powerful tool for performing high-precision time-series photometry in crowded fields and near bright stars, especially when combined with difference image analysis.